Principle and implement of automatic grader for fruit internal quality based on dielectric property - XU Fang; ZHANG Li-bin; JI Shi-ming (浙江大学学报. 农业与生命科学版)
The principle and the method of nondestructive inspection for fruit quality based on dielectric property of fruit are analyzed. A principle prototype for automatically classifying the internal quality of fruit based on the dielectric property has been developed. The construction of the prototype including mechanical、sensor and computer control, and the optimal threshold obtained by studying have been discussed. The results indicate that, using the equivalent capacitance of inspected apple as pattern characteristic for grading, the principle prototype can better classify the apple with different quality.